Implementation of Differentiated Learning Model in Islamic Religious Education Subjects at SMP Muhammadiyah 5 Surakarta - Kharisma Vina; Triono Ali Mustofa (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Each student has unique learning needs, so it is important to meet these needs so that the learning process can run optimally. At SMP Muhammadiyah 5 Surakarta, the effort to fulfill students' learning needs is closely related to the implementation of teaching and learning activities at school. To support this, innovations in teaching are needed that not only meet students' learning needs, but can also increase their interest in learning. One of the methods applied is differentiated learning, which aims to provide a more personalized learning experience that suits the individual needs of students. The research method used is a qualitative approach involving observation, interviews and documentation to obtain relevant information. The results show that differentiated learning at SMP Muhammadiyah 5 Surakarta gets a positive response from students. They find it easier to master the material because it is tailored to their learning needs.